UTILIZATION OF AGRICULTURAL PRODUCTS FOR THE MANAGEMENT AND PREVENTION STUNTING THROUGH EMPOWERING HEALTH CADRES IN JEMBER DISTRICT - Anisah Ardiana; Alfid Tri Afandi; Ardiyan Dwi Masaid; Ninna Rohmawati (Darmabakti Cendekia: Journal of Community Service and Engagements, 2020)
Background: Stunting is a problem that cannot be considered ordinary. Short toddlers (stunting) can occur due to poor nutrition and nutritional intake and lack of knowledge about stunting. Purpose: Transferring knowledge about how to prevent and manage stunting or short toddlers. Method: counseling and empowering health cadres by using tools such as LCD projectors and using leaflets and interactive discussions. Results: The implementation of this activity included advice and health cadre assistance in conducting health education to the community. Counseling for health cadres was done first to increase cadre knowledge. After that, support was given to health cadres to lead health education to the community around the village. Conclusion: After conducting mentoring activities on health cadres, which was a village program under the guidance of the University of Jember, it could increase the knowledge and motivation of cadres in conducting health education in the context of preventing and managing stunting infants.